Atherogenic Diet Accelerates Ectopic Mineralization in a Mouse Model of Pseudoxanthoma Elasticum - Jing-Yi Zhao; Joshua Kingman; Ida Joely Jacobs; Jouni Uitto; Yi Cao; Qiao-Li Li (Wolters Kluwer Health, 2020)
Abstract. Objective:. Pseudoxanthoma elasticum (PXE) is a multisystem heritable disorder caused by mutations in the Abcc6 gene. The disease is characterized by ectopic mineralization of the skin, eyes, and arterial blood vessels. Previous studies have suggested that cardiovascular complications in patients with PXE are caused in part by premature atherosclerosis. The aim of this study is to determine the effect of an atherogenic diet on ectopic mineralization. Methods:. We used Abcc6 tm1JfK mice (Abcc6 −/− mice) as an established preclinical model of PXE. The offspring at age of 4 weeks were divided into two groups and fed the standard control laboratory diet (control group) and the atherogenic diet. Serum lipid profiles and bile acids were measured, and steatosis and tissue mineralization were evaluated by histopathologic analysis and chemical calcium quantification assay, respectively. Results:. After 50-58 weeks of feeding an atherogenic diet, the concentrations of total cholesterol, low-density lipoprotein/very-low-density lipoprotein cholesterol, and bile acids were significantly higher in the Abcc6 −/− mice on the atherogenic diet (180.9 ± 14.8 g/L, 145.9 ± 12.9 g/L, and 9.7 ± 1.4 μmol/L, respectively) than in Abcc6 −/− mice on a control diet (85.2 ± 4.8 g/L, 25.1 ± 5.5 g/L, and 3.3 ± 0.5 μmol/L, respectively) (P < 0.001). Hypercholesterolemia was accompanied by extensive lipid accumulation in the liver and aorta, a characteristic feature of steatosis. The direct calcium assay demonstrated significantly increased mineralization of the muzzle skin containing the dermal sheath of vibrissae (57.2 ± 4.4 μmol Ca/gram tissue on the atherogenic diet and 43.9 ± 2.2 μmol Ca/gram tissue on control diet; P < 0.01), a reproducible biomarker of the ectopic mineralization process in these mice. An increased frequency of mineralization was also observed in the kidneys and eyes of mice on the atherogenic diet (P < 0.01). Conclusion:. These observations suggest that the atherogenic diet caused hypercholesterolemia and accelerated ectopic mineralization in the Abcc6 −/− mice. Our findings have clinical implications for patients with PXE, a currently intractable disorder with considerable morbidity and occasional mortality.